PORTABLE DIGESTER SYSTEM SEBAGAI ALTERNATIFSOLUSI DAMPAK KENAIKAN BBM UNTUK PEMENUHANKEBUTUHAN BAHAN BAKAR SKALA RUMAH TANGGAYANG PRAKTIS DAN MUDAH DIPINDAHKAN - Sugi Rahayu, Pujianto , Dyah Purwaningsih (Universitas Negeri Yogyakarta, 2013)
This activity aims to: (1) Provide advice to the public about theutilization of biogas from manure residue for the benefit of the farmers andranchers; (2) Provide an alternative solution of biogas production technologiesthat do not require farmers and ranchers to construct a plant; (3)Provide information to the public, especially peddlers, on the ergonomic andmobile aspects of portable digester system in supporting new entrepreneurs;(4) Provide trainee for manufacturing and processing skills of portabledigester system to farmers and ranchers, especially in Jatisarono Village.The training was conducted by lecturing, discussion-information,workshops, and limited dissemination. This activity involves 4 students and37 cattle breeders from 40 targeted participants. The involved cattleranchers are from Jatisarono Nanggulan Kulonprogo. Activities also involveLocal Supervisor of Agriculture and Animal Husbandry (PPL) and villageofficials. Implementation activities began on June 22, 2012 and went onuntil the workshop stage.In general, the training was successful and on target. It can be seenfrom the increasing knowledge and understanding of the manufacture ofportable cattle ranchers digester system at each stage of the PPM. It wasclearly visible from their skills to produce the PDS during the workshop.